PENGETAHUAN, SIKAP,PERILAKU DAN PENCEGAHAN VIRUS COVID 19 MAHASISWA ADMINISTRASI RUMAH SAKIT IIK PELAMONIA MAKASSAR - Resky Dewi Pratiwi (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2022)
The number of positive cases of Coronavirus Disease 2019 (Covid-19) has sharply increased following an exponential spread. One of the provinces in Indonesia outside Java with the highest number of Covid-19 cases is South Sulawesi Province, and Makassar City is the district/city with the highest number of cases in South Sulawesi. The purpose of this study is to determine the Knowledge, Attitude, Behavior, and Prevention of the Covid-19 Virus among Students of Hospital Administration IIK Pelamonia Makassar. This research is a descriptive quantitative study conducted at the Pelamonia Health Science Institute Kesdam XIV Hasanuddin Makassar in 2020. The sample in this study consisted of 119 respondents from the 2016, 2017, and 2018 cohorts. The method used in this research is non-random sampling technique. Data collection tools used a questionnaire in the form of a Google form link distributed to students through social media groups. The collected data were processed using the SPSS application and presented in tables and descriptions. The results showed that the majority of students have Very Good knowledge, with the least having Good knowledge. The majority of students have Good attitudes, with the least having Very Good attitudes. The majority of students have Very Good behavior, with the least having Good behavior. The majority of students have Good prevention of Covid-19, with the least having Very Good prevention. It is recommended to improve the understanding and knowledge of students who currently have a good level of knowledge through additional educational programs, seminars, or workshops focusing on specific aspects related to Covid-19.